Cerebellar Mutism after Posterior Fossa Surgery - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1997)
Six children, aged 6 to 12 years, who developed cerebellar mutism after surgery for a posterior fossa mass or as a result of trauma are reported from the Children's Hospital, Los Angeles, CA.